(3x+7)=(5x-3)

Simple and best practice solution for (3x+7)=(5x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+7)=(5x-3) equation:


Simplifying
(3x + 7) = (5x + -3)

Reorder the terms:
(7 + 3x) = (5x + -3)

Remove parenthesis around (7 + 3x)
7 + 3x = (5x + -3)

Reorder the terms:
7 + 3x = (-3 + 5x)

Remove parenthesis around (-3 + 5x)
7 + 3x = -3 + 5x

Solving
7 + 3x = -3 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
7 + 3x + -5x = -3 + 5x + -5x

Combine like terms: 3x + -5x = -2x
7 + -2x = -3 + 5x + -5x

Combine like terms: 5x + -5x = 0
7 + -2x = -3 + 0
7 + -2x = -3

Add '-7' to each side of the equation.
7 + -7 + -2x = -3 + -7

Combine like terms: 7 + -7 = 0
0 + -2x = -3 + -7
-2x = -3 + -7

Combine like terms: -3 + -7 = -10
-2x = -10

Divide each side by '-2'.
x = 5

Simplifying
x = 5

See similar equations:

| 14=x*26 | | 2(x+7)+6=26 | | (5x-1)=(6x-3) | | 2=5(x+9)8x | | T=p-ir | | 4a^2-147=a^2 | | (y-2)-(y+1)=(y-3)-2 | | y=arcsen(3x) | | -(2x+5)=-21 | | 5/8m=60 | | 7-6/5x=8 | | 2(n)+5=45 | | 3x+1-2=7-2 | | log(x)+0.5*x-1=0 | | ln(x)+0.5*x-1=0 | | Y=7/4x-6 | | 4n-7n=-2 | | 3x-3=5y+1 | | Tg(4x)=0.1 | | 11b-2b=72 | | y=arcsen(2x) | | http://www.thelearningodyssey.com/Assess/DPT/QIEImagesStorage/AQ5MA/AQ5MA_MA55212_12_stem1_1.gif | | -1/9t=8 | | 3sin(x+10)=4cos(x-10) | | 5x-3(2x+1)=21+x | | 4x+10+3x=37x | | X^2+y^2+z^2=77 | | (5x-3y)(2x-4y)=0 | | 8-7a=-6a+8 | | 2x-3x+x= | | 6x-14x+16=46 | | -4a^7+8a^6-2a^5= |

Equations solver categories